Como os economistas discordam: um ensaio metodológico sobre o "contexto da descoberta" em economia - Cavalieri, Marco Antonio Ribas (Estudos Econômicos (São Paulo), 2007)
This article concerns the methodology of investigations about the history of economic thought from a plural perspective, considering the variety of approaches as the strongest feature in the knowledge of economic phenomena. Here it is presented a suggestive methodology to study the birth of schools of thought, what we call the "context of discovery" in economics. We argue about the relations between the social reality, which is historically and geographically specific, and the theories and new approaches that appear in these contexts. The methodology suggested ranges from the schools of thought characterization, by the means of Kuhn and Lakatos categories, to the treatment of anachronism, which is embedded in all intellectual historiography work. As a result, an interpretative model is designed, to be used in future studies about authors and schools of economic thought.